Artificial Intelligence in Education: Revolutionizing Teaching and Learning - Kumar, Amitabh (Journal of Asian Primary Education (JoAPE), 2024)
Artificial Intelligence (AI) is transforming education by enhancing personalized learning, automating routine tasks, and improving both student engagement and teaching effectiveness. However, challenges such as inadequate teacher training, infrastructural limitations, and data privacy concerns hinder AI's widespread adoption in educational settings. This paper presents findings from a survey of 150 educators and classroom observations, highlighting the impact of AI on teaching and learning. Results show significant improvements in student engagement, academic performance, and a reduction in teacher workload in AI-enabled classrooms. Despite the potential of AI, addressing key challenges is critical for its successful integration into education. The paper concludes with recommendations for training, infrastructure development, and ethical considerations.